Two Enantiomorphic MgII/Carboxylate Coordination Polymers Produced from Spontaneous Resolution with an Achiral Bipyridyl Dicarboxylate Ligand. Issue 7 (15th January 2013) - Zhang, Qingfu; Hao, Hongguo; Zhang, Haina; Wang, Suna; Jin, Juan; Sun, Dezhi
Abstract: Two enantiomorphic Mg II /carboxylate coordination polymers [Mg(bpda)(H2 O)4 ] n (1M and1P ) have been obtained by spontaneous resolution from achiral precursors, 2, 2′‐bipyridyl‐3, 3′‐dicarboxylic acid (H2 bpda) and Mg(NO3 )2 · 6H2 O, upon crystallization without any chiral auxiliary. X‐ray structural analysis shows that chiral transmission from molecular axially chiral conformations to crystal chirality is established through concerted coordination and H‐bonding interactions. In addition, the CD data, and the thermal and photoluminescence properties in the solid state have also been discussed. Abstract : Two enantiomorphic Mg II /carboxylate coordination polymers [Mg(bpda)(H2 O)4 ]n (1M and1P ) have been obtained by spontaneous resolution from achiral precursors, 2, 2′‐bipyridyl‐3, 3′‐dicarboxylic acid (H2 bpda) and Mg(NO3 )2 · 6H2 O, upon crystallization without any chiral auxiliary.